ANALYSIS OF COAST LINE CHANGES USING LANDSAT IMAGERY AT TAPIAN NAULI DISTRICTCENTRAL TAPANULIREGENCYNORTH SUMATERA PROVINCE - Amari, Tomi; Galib, Musrifin; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Beach is a geographical which is be composed of sand and is located in the coastal area. The coastal area is the restrictions between coastal and sea. Beaches can change due to natural and human influences. The research was conducted in July 2018 at Tapian Nauli I, Central Tapanuli Regency, North Sumatera Province.The aim this research is to map and analyze the rate of shoreline change using Landsat Imagery. Imagery data downloaded from USGS site and then to analyze using ER Mapper and Arc Gis application.The results show that there has been a change in the coastline (abrasion and accretion). The current velocity range 0.09 - 0.12 m/s. The lowest of wave energy is 1.568 Nm / m² and the highest is 5.096 Nm/m². The lowest of abrasion is 0.538 m/year and the highest is 3.36 m/year. Keywords: Coastline, Tapian Nauli, Landsat Imagery, Abrasion, Accretion